Management of Ventenata dubia in the inland Pacific Northwest with indaziflam. (December 2019) - Koby, Lindsay E.; Prather, Timothy S.; Quicke, Harold; Beuschlein, Jared; Burke, Ian C.
Abstract: Ventenata [ Ventenata dubia (Leers) Cross] is a winter annual grass relatively new to the inland Pacific Northwest that is capable of displacing desired vegetation. Indaziflam was evaluated for the management of V. dubia on two Conservation Reserve Program (CRP) sites near Moscow, ID, and Pullman, WA. While perennial grasses were dormant, applications of indaziflam in mixture with various herbicides were made in spring 2016. Treatment effects were evaluated for 2 yr by visual assessments of community composition and canopy cover of V. dubia and other non-weedy species (assessments occurred 3 to 6 mo after treatment, depending on location) and by representative cover class assessments. Biomass samples of all plant species were collected in the summer of 2017. Reduced V. dubia cover was observed in 2016, except when glyphosate was used alone. In 2017 indaziflam applied alone or in mixture with rimsulfuron effectively controlled V. dubia with minimal impact on desirable vegetation. Plant biomass from nontreated plots averaged 40 g m −2 for V. dubia and 100 to 179 g m −2 for perennial grasses. Plant biomass averaged <11 g m −2 for V. dubia and 371 to 490 g m −2 for perennial grasses when indaziflam at 102 g ai ha −1 plus glyphosate at 474 g ai ha −1 was applied. Smooth brome ( Bromus inermis Leyss.) biomass was positively associated with the reduction of V. dubia, and there was a decrease in diversity associated with the removal of V. dubia through effective treatments. Indaziflam is an effective tool for the management of V. dubia in perennial grass stands, and spring applications of indaziflam should be in mixture with herbicides with POST activity.